'Give people work, and the blood pressure will sink': lay engagement with cardiovascular risk factors in North Karelia in the 1970s. (17th February 2016) - Jauho, Mikko
Abstract : In high-income countries such as Finland, personal healthcare is organised around the management of lifestyle risks and minimisation of such risks forms a key part of public health policy. While the scientific development of the lifestyle risk model has been thoroughly studied, there has been less research on the history of popular experiences of the model. In this article, I examine lay people's response to a pioneering heart disease prevention programme in north-eastern Finland in the 1970s, the North Karelia Project, which promoted the lifestyle risk model. I use archival data from early 1970s that recorded the project interactions with the local population and their reactions to the project. I show that although local residents in North Karelia responded positively to the project, they did not necessarily subscribe to its preventive and risk minimising objectives. In an area of limited health resources, the project provided local residents with access to medical expertise. Local reactions indicated a clash of a cultural notion of illness embedded in the social life-world of Karelians with a specific rationality of government emphasising individual responsibility vis-à-vis heart conditions. Local residents who were critical of the public health risk model tended to minimise the role of lifestyle risk factors in cardiovascular disease causation or subsumed these factors into a more encompassing explanation that stressed the effects of the on-going structural social change in the area, highlighting the sense of loss caused by the waning of traditional small farm existence and their anxiety about the resulting economic and social insecurity.